mip causes hyperinnervation of a retinotopic map in Drosophila by excessive recruitment of R7 photoreceptor cells. - Buckles, G.R.; Smith, Z.D.; Katz, F.N. (Neuron, 1992)
The two central photoreceptor neurons of the Drosophila eye, R7 and R8, form a retinotopic map in the optic lobe of the fly brain. We have developed a technique that allows us to visualize the projections of these neurons with high resolution. Using this technique, we have identified a new mutant, mip (more inner photoreceptors), in which this map shows a striking hyperinnervation. The extra terminals in the brain derive from an excessive recruitment of sevenless-independent R7 photoreceptor cells during eye development. The original R7, however, remains sevenless responsive. The behavior of this gene suggests that recruitment to the R7 pathway, and possibly to multiple programs in ommatidial assembly, is partially regulated by inhibition.